The Predictive Control Method of VAV Air Conditioning System - Jiejia LI; Xiaofeng LI; Yang CAO (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the characteristics which variable air volume air conditioning system is multi-variable, nonlinear and uncertain system, normal fuzzy neural network is hard to meet the requirements which dynamic control of multi-variable. In this paper, we put forward a recursive neural network predictive control strategy based on wavelet neural network model. Through recursive wavelet neural network predictor on line established controlled object’s mathematical model, and using Elman neural network controller on line corrected information we get, thus to improve control effect. The simulation results show that recursive wavelet neural network predictive control has stronger robustness and adaptive ability, high control precision, better and reliable control effect and other advantages. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3244